If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(0.3r + 1) = 23 + -0.1r Reorder the terms: 2(1 + 0.3r) = 23 + -0.1r (1 * 2 + 0.3r * 2) = 23 + -0.1r (2 + 0.6r) = 23 + -0.1r Solving 2 + 0.6r = 23 + -0.1r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '0.1r' to each side of the equation. 2 + 0.6r + 0.1r = 23 + -0.1r + 0.1r Combine like terms: 0.6r + 0.1r = 0.7r 2 + 0.7r = 23 + -0.1r + 0.1r Combine like terms: -0.1r + 0.1r = 0.0 2 + 0.7r = 23 + 0.0 2 + 0.7r = 23 Add '-2' to each side of the equation. 2 + -2 + 0.7r = 23 + -2 Combine like terms: 2 + -2 = 0 0 + 0.7r = 23 + -2 0.7r = 23 + -2 Combine like terms: 23 + -2 = 21 0.7r = 21 Divide each side by '0.7'. r = 30 Simplifying r = 30
| -9+4(x-3)=-4x+3 | | 3(x+3)-sx+7=x+4 | | .04x+.07(12000-x)=720 | | 3g-6(g-8)=32 | | z^2=(z-4)(z+5) | | 1000=40x^2 | | 18-3.8t=7.39-1.9t | | 6x^2+72x+210=0 | | a^5-6a^4+a-6=0 | | -84=6g | | 8+6/-4=12 | | 1.5x+10.3=3.4x-3 | | 57=3+6(4x-7) | | 7(4+7b)=-70 | | 18-3.8t=7.36-19t | | 2x^2-102x+14=0 | | 5n+4-8n=(-5) | | (u+8)(u-4)= | | -24=4(2-8r) | | -(1+6x)=14-x | | ln(8-6x)-2ln(x)=ln(2) | | 25-18+4(-2)= | | 3-4q=10q+100 | | W+1-5=2w | | 3x^15*x-36=0 | | 5x^2-27x+10=0 | | 7=x/2+5 | | 5y-3(y-2)+3= | | Q=xy-xy^2 | | 5+2x=3(2x+4)-5(x-2) | | 10-4(2w+1)=6w-4(6+w) | | -38=2k |